1970
DOI: 10.3329/jbsp.v6i1.8061
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Status in Neonatal Jaundice Patients and Its Relationship with G6PD Deficiency

Abstract: Background: The role of hemolysis in the pathophysiology of neonatal jaundice in patient with G6PD deficiency. Objectives: To observe the hematological status of hyperbilirubinemic neonates and its corelation with G6PD deficient neonates. Methods: The study was conducted on 90 male, term neonates with jaundice, age ranged from 3 to 12 days (Group B) in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU) between 1 st July 2007 to 30 th June 2008. On the basis of total serum bilirub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These findings support the postulation of the mechanism of neonatal jaundice in G6PD deficiency other than hemolysis. 29 In a study conducted in Bangladesh, Akter et al 30 showed that hemoglobin concentration, hematocrit, total count of red blood cell and reticulocyte count showed non-significant positive correlations (r=0.745, r=0.205, r=0.329, r=0.104) with erythrocyte G6PD level in deficient neonates. But in the present study, there was highly significant negative correlation between G6PD enzyme and hemoglobin levels (r= -0.314, p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the postulation of the mechanism of neonatal jaundice in G6PD deficiency other than hemolysis. 29 In a study conducted in Bangladesh, Akter et al 30 showed that hemoglobin concentration, hematocrit, total count of red blood cell and reticulocyte count showed non-significant positive correlations (r=0.745, r=0.205, r=0.329, r=0.104) with erythrocyte G6PD level in deficient neonates. But in the present study, there was highly significant negative correlation between G6PD enzyme and hemoglobin levels (r= -0.314, p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Wet, dry or frozen fava bean ingestion of grains, even if the mother eats fava beans can cause hemolysis in newborn infants through breast milk may occur (Luzzatto, 2001). Individuals with G6PD deficiency hemolytic effect caused by the beans contained many glycosides that are toxic due to the visin and konvisin (Beutler, 1994, Akhter, et al, 2011. In addition, β-glucosides in bean seeds, maturity stage of fava beans attain very high amounts causing a severe course of hemolytic crisis (Katz & Schall, 1979, Greene, 1993, Beutler, 1994.…”
Section: 5mentioning
confidence: 99%